The Application Of The Rules Of Syari'ah As The Effect Of Islamic Economic Education Improvement - Moh. Arifin ,Ridan Muhtadi, Denizar Abdurrahman Mi’raj (ACTIVA: Jurnal Ekonomi Syariah, 2018)
Since the enactment of Law No. 22 of 1999 on Regional Autonomy which had been renewed by Law No. 32 of 2004 and renewed again Law No 24 of 2014 on Regional Government as the implementation of regional autonomy, Local Government has wide authority in the management of its area. With this wide authority, the implementation of the Regional Regulation (PERDA) of Islamic Sharia becomes more in line with the local Islamic wisdom in Madura. Currently, the development of Islamic economic education has become an interesting topic in Indonesia. After the Asian economic crisis in 1997, the neo-classical economic approachs got harsh criticism. Then it makes the widespread of Islamic economic education’s discourse. Especially for Indonesia as the largest Muslim population country. Global financial crisis in 2008 increasingly made Islamic economics ogled many economists and practitioners as one alternative to the prevention of economic crisis. Islamic Economic Education in Indonesia is very important. Especially if you see the growth of the financial industry and sharia business is quite rapid. So it is very necessary for the effort of planting the science of divine economics to the areas especially in Madura. To improve sharia economic education in Madura, the need for proper regulation and in accordance with the local wisdom of religious Madurese by applying and enacting the Sharia law. Keyword: Madura, Application of Sharia law, and Islamic Economic Education.